A munkajog területén megvalósuló egyenlő bánásmód követelménye, valamint megsértésének módjai az Európai Bíróság és a magyar bírói gyakorlat tükrében - Duró, Edit (Debreceni Jogi Műhely, 2014)
Employment and occupation are crucial to ensuring equal opportunities for all and in large measure contribute to the full participation of citizens in economic, social and culture life. However, many cases of discrimination have been identified in the field of employment and the labour market.In this study I try to examine how the equal treatment works in the EU Law and Hungarian national law, and I try to present the case-law of the European Court of Justice and the Hungarian Courts in this area. The first part of the study deals with the definition of key concepts (direct discrimination, indirect discrimination, harassment), and include its legal background – with respect to the directives of the European Parliament and the Council, and the Hungarian legislation. The second part tries to describe the legal concept of indirect discrimination, mentioned as justification (statutory derogation, objective justification). And finally I try to present the special burden of proof, which is used in discrimination cases.